Sustainability disclosure as a mediator: The effects of profitability, leverage, and institutional ownership on firm value in Indonesian Banking (2021–2024) - Anggya Julliet Jennyver Mangundap; Jullie Jeannete Sondakh; Hendrik Gamaliel (Yayasan Widyantara Nawasena Raharja, 2026)
This study examines the effects of profitability, leverage, and institutional ownership on sustainability disclosure and firm value among banking companies listed on the Indonesia Stock Exchange during 2021–2024, addressing persistent variation in disclosure quality despite the rapid rise in sustainability-reporting compliance. Using a quantitative, explanatory design with Structural Equation Modeling–Partial Least Squares (SEM-PLS), the study analyzes 136 firm-year observations from 34 banks selected through purposive sampling. The structural model explains 26.2% of the variance in firm value (R² = 0.262) and 10.8% of the variance in sustainability disclosure (R² = 0.108). Leverage (β = −0.214; p = 0.004) and institutional ownership (β = −0.273; p = 0.001) significantly and negatively affect sustainability disclosure, whereas profitability shows no significant effect (β = 0.020; p = 0.819). Sustainability disclosure (β = 0.392; p < 0.001), profitability (β = 0.135; p = 0.001), and institutional ownership (β = −0.176; p = 0.046) significantly affect firm value, while leverage exerts no significant direct effect (p = 0.206). Sustainability disclosure fully mediates the leverage–firm value relationship (p = 0.009) and partially mediates the institutional ownership–firm value relationship (p = 0.002), but does not mediate the profitability–firm value relationship (p = 0.820). By repositioning sustainability disclosure as a mediating mechanism and applying a banking-adjusted GRI checklist within a highly leveraged, capital-regulated industry, this study provides novel evidence that sustainability disclosure functions as a critical non-financial channel linking financial and governance characteristics to firm value. The findings offer practical implications for bank management seeking to strengthen disclosure quality and for regulators, including Indonesia's Financial Services Authority (OJK) and the Indonesian Institute of Accountants (IAI), in advancing forthcoming sustainability-disclosure standards.